Branching function of terminal phosphate groups of polyisoprene chain. (12th June 2019) - Li, Shiqi; Tang, Maozhu; Huang, Cheng; Zhang, Rong; Wu, Jinrong; Ling, Fangwei; Xu, Yun-Xiang; Huang, Guangsu
Abstract: The branching structure formed by α terminal of natural rubber (NR) was believed to be critical for its superior mechanical properties. However, it is challenging to unravel and mimic the relationship between the terminal structures and properties of NR due to the complexity of the system. Herein we synthesized a model compound containing phosphate groups at the end of the polyisoprene rubber to explore the role of α-terminal. After a series of tests, it is found that the phosphate groups formed branching points with or without iron ions. TEM test showed that sizes of aggregates formed by phosphate groups changed to be smaller after addition of FeCl3 . Water contact angle test verify the formation of branching structures. Rheology test showed that branching structures increased their storage modulus G' compared to linear polymer. The effects of phosphate groups aggregations on the chain dynamics were also investigated. Dielectric relaxation analysis indicated that the branching structure formed by phosphate groups confined the chain movement. All the above results help us to get a deeper understanding on the structural formation and function about α-terminal groups of NR. Graphical abstract: Image 1 Highlights: A model compound containing phosphate groups at the end of the polyisoprene chain was synthesized. The branching structure formed by phosphate groups was confirmed. The effects of branching structure on storage modulus and chain dynamics were investigated.